The Effect of Blanching Methods and Extractions on Quality of Edamame Milk Product - Melki Yohanes Amtiran; I Gede Pasek Mangku; Anak Agung Made Semariyani (SEAS (Sustainable Environment Agricultural Science), 2018)
This research was conducted with the aim to know the study the effect of blanching method and extraction on edamame milk characteristics. The design used in this study was a Randomized Block Design (RBD) with a factorial pattern consisting of two factors (blanching methods and extraction) and two replications. The analysis is done by objective and subjective. The actual analysis including of water content, pH, total soluble solids (TSS), protein content, ash content, and shelf-life. Individual observations include assessment of color, viscosity, flavor, and overall reception using the scoring method by SNI 3141.1: 2011. The result showed that the blanching method and extraction could maintain the characteristics up to 18 days of storage with features: water content 90.10%, pH 7.09, TSS, 15,90, protein content 1.25 (below standard quality), ash content 0.48, 5.93 colors, 5.60 flavor, 5.73 viscosity, 5.87 taste, and reception overall (rather like-like).